ANALISIS YURIDIS PERTIMBANGAN HUKUM PENGADILAN NEGERI SINGKAWANG DALAM PUTUSAN PERKARA NOMOR 56/Pdt.G/2018/PN Skw - NIM. A1011151225, BIMA HIDAYATULLAH (Fakultas Hukum Universitas Tanjungpura, 2022)
ABSTRACTThe court is an institution formed by the state to handle cases submitted by the community to obtain justice. However, there are justice seekers who feel that their rights have not been fulfilled, they do not get legal certainty for the rights they are demanding resulting in justice seekers experiencing material losses in the form of substantial costs, the time for completing cases is long because the court's decision was seeking justice cannot accommodate the fulfillment rights of justice seekers.The writing of this law was examined based on the formulation of the problem